Variation of the redox properties and coordination chemistry of redox-active aromatic diguanidine ligands with the substitution pattern - Schulz, Maximilian; Poddel'sky, Andrey; Bohnert, Hannah A.; Eckhardt, Frederik; Hirner, Lukas; Leingang, Simone; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2025)
The redox properties of organic molecules like quinones are generally tuned by substitutions at the π-conjugated system or by changing the size of the π-conjugated core. Here, it analyzes the change of the redox properties within a series of isomeric molecules, differing only in the substitution pattern of the groups responsible for the redox activity. The seven redox-active molecules studied in this work, all composed of two guanidino and two thiolato substituents attached to a benzene core, can be reversibly oxidized to the dications, with the radical monocations as intermediate redox states, but the redox potentials and the potential separations between the first and second redox steps vary significantly with the substitution pattern. Distinct hyperfine coupling patterns observed in the EPR spectra of the radical monocations, in alliance with quantum-chemical calculations are used to show that, depending on the substitution pattern, semiquinonato-type or allyl radical-allyl cation-like structures are adopted. Reactions with CuII salts give different results depending on the substitution pattern, the copper coligands, and the guanidino group. Paramagnetic dinuclear CuII complexes with the neutral molecule as bridging ligand or diamagnetic CuI compounds with the redox-active molecules in their oxidized, dicationic redox state are formed.
Gesehen am 20.11.2025